The use of a quartz crystal microbalance as an analytical tool to monitor particle/surface and particle/particle interactions under dry ambient and pressurized conditions: a study using common inhaler components - Turner, Nicholas W.; Bloxham, M.; Piletsky, Sergey A.; Whitcombe, Michael J.; Chianella, Iva (Royal Society of Chemistry, 2016)
Metered dose inhalers (MDI) and multidose powder inhalers (MPDI) are commonly used for the treatment of chronic obstructive pulmonary diseases and asthma. Currently, analytical tools to monitor particle/particle and particle/surface interaction within MDI and MPDI at the macro-scale do not exist. A simple tool capable of measuring such interactions would ultimately enable quality control of MDI and MDPI, producing remarkable benefits for the pharmaceutical industry and the users of inhalers. In this paper, we have investigated whether a quartz crystal microbalance (QCM) could become such a tool. A QCM was used to measure particle/particle and particle/surface interactions on the macroscale, by additions of small amounts of MDPI components, in the powder form into a gas stream. The subsequent interactions with materials on the surface of the QCM sensor were analyzed. Following this, the sensor was used to measure fluticasone propionate, a typical MDI active ingredient, in a pressurized gas system to assess its interactions with different surfaces under conditions mimicking the manufacturing process. In both types of experiments the QCM was capable of discriminating interactions of different components and surfaces. The results have demonstrated that the QCM is a suitable platform for monitoring macro-scale interactions and could possibly become a tool for quality control of inhalers.